Effect of Al addition on microstructure and mechanical properties of as-cast Mg-4Y-3Nd alloy. Issue 2 (17th January 2020) - Wang, Lei; Guo, Erjun; Jiang, Wenyong; Feng, Yicheng; Zhao, Sicong; Fu, Yuanke; Chen, Hongtao
ABSTRACT: The microstructure and mechanical properties of Mg-4Y-3Nd-xAl ( x  = 0, 0.6, 0.9, 1.2, 1.5, 2.0%) alloys were investigated in the present work. The results show that the addition of Al can refine the grain of as-cast Mg-4Y-3Nd alloy significantly. The refining effect increases first and then decreases with increasing Al addition. The grain size of Mg-4Y-3Nd alloy is smallest when the Al addition is 1.5%. The reason for refinement is that the in-situ Al2 RE particles reacted Al with RE can serve as for α-Mg matrix. The orientation relationship between Al2 RE particles and α-Mg was determined by TEM analysis: [ 101 ] A l 2 R E ∥ [ 1 1 ¯ 00 ] M g ( 2 ¯ 22 ) A l 2 R E ∥ ( 0002 ) M g . The effective size of Al2 RE particle served as heterogeneous nucleation site is 1 ∼12 μm. In addition, the strength and ductility of the alloy increase with the increase of Al addition. The Mg-4Y-3Nd-Al alloy with the higher mechanical properties can be attributed to fine grain strengthening and second phase strengthening.